Clinical Comparison of Topcon CT-80 Non-contact Tonometer with Goldmann Applanation Tonometer in Nepalese Population - Shrestha, Shristi; Kaini, Khemraj (Nepal Journal of Medical Sciences, 2022)
Introduction: Goldmann applanation tonometer (GAT) is the gold standard method of measuring the intraocular pressure (IOP) but, it is subjected to intra and inter-reading variability, risk of cross-infection, and possible damage to the cornea. A non-contact tonometer (NCT) reduces the risk of cross-infection, is not operator dependent, and can be used in post-refractive surgery patients. Therefore, the study aims to correlate the IOP readings obtained by non-contact tonometer and GAT. Methods: A hospital-based, prospective, cross-sectional descriptive study was carried out in the Department of Ophthalmology, Manipal Teaching Hospital, Pokhara. One hundred and twenty cases were recruited in the study from June 2019 to May 2020. The IOP was taken from NCT followed by GAT. Results: Mean IOP was 17.03±5.14 mmHg for GAT and 16.49 mmHg±5.35 mmHg for NCT and this difference was statistically insignificant (p=0.2). The difference in the mean value increased with higher intraocular pressure which was statistically significant (p<0.05). The NCT underestimated the IOP in lower intraocular pressures whereas it overestimated the IOP in higher intraocular pressures which were statistically significant (p<0.00). The overall mean ± SD difference between GAT and NCT measured IOPs was 0.53±2.07 mmHg. Bland-Altman analysis revealed that 95% limits of agreement (LoA) ranged from -3.53 to 4.60 mmHg. Correlation analysis showed a high correlation between NCT and GAT (r=0.92). Conclusion: NCT compared favorably with GAT but it tends to yield lower IOP readings within the normal range and higher IOP readings at a higher range. NCT can be used as a fair tool for screening purposes.